1) What is f(-2) for f(x) = ?
2) What is f(-4) for f(x) = ?
3) Find (f – g)(x) if f(x) = 2x – 3 and g(x) = 4x + 8.
4) Find (f + g)(x) if f(x) = and g(x) = -x - 3.
You are missing information in some cases.
1) You need to know the function f(x) and replace x by -2
Ex: f(x)=x+2 then f(-2) = -2+2=0
2) You need to know the function f(x) and replace x by -4
Ex: f(x)=x+2 then f(-4)= -4+2 = -2
3) You have all the information:
(f-g)(x) = f(x) - g(x) = 2x-3 - (4x+8)
= 2x -3 - 4x - 8 changing the signs inside the parenthesis
= (2x - 4x) + (-3 - 8) Regrouping
= -2x + (-11 ) because -a-b = - (a+b)
= -2x - 11 because +*- = -
4) You have g(x) but you need to have also f(x)
(f+g)(x) = f(x) + g(x) = f(x) + (-x-3) = f(x) - x - 3
Content will be erased after question is completed.
Enter the email address associated with your account, and we will email you a link to reset your password.
Forgot your password?